Fatigue strength of hot-stamped spot welded joints*—study on spot welding tailored blank technology. Issue 4 (3rd April 2018) - Fujimoto, Hiroki; Ueda, Hideki; Nakayama, Eisuke; Ueji, Rintaro; Fujii, Hidetoshi
ABSTRACT: Hot stamping spot welding tailored blank (TB) technology is a process to produce spot welded automotive body parts by the following process: Spot welding steel sheets in lap configuration → Hot stamping (Heating to about 900°C → Quenching and forming in water-cooled die → Shot blasting to remove scale). This process has the advantage of producing high strength lap welded automotive body parts without increasing the number of forming dies. In this study, the tensile shear fatigue strength of the spot welding TB joints (Spot welding → Hot stamping) and conventional spot welded joints (Hot stamping → Spot welding) of the 1500MPa class uncoated boron steel sheets are compared. The obtained results are as follows. The fatigue life of the spot welding TB joints was more than two times longer than that of the conventional spot welded joints. The long fatigue life of the spot welding TB joints was not caused by the heating and quenching process but by the shot blasting process after heat treatment. Shot blasting on the outer sheet surface caused the high compressive residual stress on the outer surface and did not affect the residual stress on the lapped surface. Shot blasting on the outer sheet surface increased the initiation life of fatigue crack which occurred on the lapped surface and also reduced the crack propagation speed which propagates from the lapped surface to the outer surface. FE-analysis suggested that compressive residual stress on the outer surface reduce the opening of sheet separation of joints in fatigue tests and reduce the maximum principal stress around the edge of corona bond.